The Correlation between Teachers’ Personality and Students’ Motivation in Learning English - Muinuddin M Dyah, Mutmainna; Mustakim, Mustakim; Ismail, Ismail (Majesty Journal, 2022)
This research examined the correlation between teacher’ personality and students’ motivation in learning English. The research population consisted of all second grade of SMAN 2 Enrekang. A total of 66 students were selected as sample to Stratified random method. The data collection tool was teacher personality and students’ motivation questionnaires. The indicators of teacher personality were adapted from the Minister of National Education Regulation of the Republic of Indonesia Number 16 (2007) regarding standards of academic qualifications and teacher competencies and the indicators of student motivation were instrumental and integrative motivation. The expert validation was used in this research. The data analysis technique used the product moment correlation formula. The result showed the significance (2-tailed) value of the teacher personality and student motivation variables were at 0.000 < 0,05 and had a degree of relationship 0.832 (very strong correlation). This research has shown that teacher personality was correlated with students’ learning motivation.